PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Rofih Lestari; Khuzaeni (Journal of Research and Publication Innovation, 2025)
This study focuses on automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The main objective of the study is to analyze the effect of cash turnover and receivable turnover on profitability, measured by Return on Assets.The research method employed is quantitative with a asosiatif approach, and the data analyzed includes financial statements from the IDX. The results reveal that cash turnover partially has a positive and significant effect on changes in Return on Assets, while receivable turnover partially has no significant effect. However, simultaneously, cash turnover and receivable turnover have a significant effect on changes in Return on Assets